Effects of cytoprotective antioxidants on lymphocytes from representative mitochondrial neurodegenerative diseases - Goldschmidt, Ruth; Arce, Pablo M.; Khdour, Omar M.; Collin, Valérie C.; Dey, Sriloy; Jaruvangsanti, Jennifer; Fash, David M.; Hecht, Sidney M. (Bioorganic & medicinal chemistry, 2013)
Two new aza analogues of the neuroprotective agent idebenone have been synthesized and characterized. Their antioxidant activity, and ability to augment ATP levels have been evaluated in several different cell lines having suboptimal mitochondrial function. Both compounds were found to be good ROS scavengers, and to protect the cells from oxidative stress induced by glutathione depletion. The compounds were more effective than idebenone in neurodegenerative disease cells. These novel pyrimidinol derivatives were also shown to augment ATP levels in coenzyme Q10-deficient human lymphocytes. The more lipophilic side chains attached to the pyrimidinol redox core in these compounds resulted in less inhibition of the electron transport chain and improved antioxidant activity.